(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current state of digital transformation activities at commune health stations in Thai Binh province (formerly) in 2024 and some related factors. Methods: A cross-sectional descriptive study was conducted on a total of 120 commune health stations in Thai Binh province from February to May 2024. Information was collected using a pre-structured questionnaire on digital transformation activities at commune health stations in Thai Binh province with descriptive statistics. Results: Of the staff directly using information technology software at commune health stations, 59.2% were under 40 years old; 80% were female; pharmacists accounted for the highest percentage at 45.8%, medical assistants at 22.5%, nursing at 10%, and other staff at 21.7%. The proportion of staff with intermediate-level qualifications is 22.5%, college-level qualifications is 54.2%, and university-level qualifications is 23.3%. 100% of commune health stations have computers, 75% have three or more computers, and 50.8% of stations have computers that are functioning normally. 100% of commune health stations have internet access, and 80% of the internet connections are functioning normally. 23.3% of staff are aware of Decision 3532/QD-BYT dated August 12, 2020, of the Ministry of Health, and 28.3% have received training and guidance on using the commune health station management information system software. Correct knowledge regarding the need for annual digital transformation planning at commune health stations was high in three groups: university graduates (50%), those with less than 10 years of experience directly using information technology software (38.5%), and those under 40 years old (38.9%). Correct knowledge regarding the steps to handle hardware information technology problems was also high in three groups: intermediate level education (40.7%), those with 10 years or more of experience directly using information technology software at commune health stations (38.2%), and those under 40 years old (44.4%). The differences were not statistically significant due to the small sample size (p > 0.05). Conclusions: The current state of information technology infrastructure and knowledge of staff directly using information technology software at commune health stations in Thai Binh province remains limited. It is necessary to increase investment in purchasing additional computers, repairing and upgrading existing computers to improve their operational quality, upgrading the quality of internet connections, and promoting training activities to enhance the knowledge and practical skills of staff directly using information technology software at commune health stations.